Changes in cycling kinematics in function of exercise intensity and association with injury prevalence in amateur road cyclists: a 3D kinematic motion analysis study using statistical parametric mapping - Jacobs, E.; Schuermans, J. (British Journal of Sports Medicine, 2021)
Background Road cycling is one of the most popular endurance sports worlwide. Due to its cyclic character, the prolonged flexion posture and significant training volumes, it is associated with a high overuse injury prevalence. To prevent these injuries, control of cycling posture is thought to be imperative. To what extent cycling posture relates with susceptibility to injury, has not been investigated so far.